HEGEMONI MASKULINITAS DALAM POLITIK: : Kajian Tentang Problematika Calon Legislatif Perempuan Dalam Politik Representasi Pemilihan Legislatif Tahun 2019 - Kadji, Jurisman; Husnan, Moh. Ihsan (Farabi, 2021)
The appearance of women as legislative candidates in the arena of power is an interesting thing. In the implementation of simultaneous elections in 2019. Although there is an increase in the representation of women candidates. But in fact the 30 percent quota in parliament is difficult to fulfill. One of the problems is the bargaining position of female legislative candidates in legislative elections which is still unequal compared to male legislative candidates. The hegemony of men over women does not occur in the private sphere but also in the public sphere. Therefore, the purpose of this study seeks to describe the problem of women's representation in the practice of political representation that occurs in the public sphere, especially at the local political level. In this research, the researcher uses a qualitative method. Meanwhile, data collection is done through data triangulation. The results of existing research show that the problem does not come by itself, but there are internal and external factors in political parties that still place women in a subordinate position to men. Internal party factors, resource capacity, and the influence of patriarchal culture are the dominant factors that hinder the representation of women in the 2019 legislative candidate recruitment process. This happens because political parties are the arena and space for structuralism that is very patriarchal and pragmatic so that hegemonic masculinity in this political representation practice is still well maintained.